Stem Water Storage Dynamics in Amazonian Palms and Dicotyledonous Trees - Lion R. Martius; Thaise Emilio; Thales Moreira de Lima; Pablo Sanchez-Martinez; Antonio C. L. da Costa; Maurizio Mencuccini; Patrick Meir (Tropical Plant Biology, 2026)
Stem water storage plays a key role in buffering plants against drought, yet continuous measurements of stem water content remain rare in tropical forest trees. Using frequency domain reflectometry (FDR) sensors, we continuously monitored stem water storage and mobilisation dynamics in co-occurring palm and dicotyledonous tree species in the eastern Amazon during the extreme 2023 drought. This approach provides, to our knowledge, the first temporal high-resolution dataset of stem hydration in Amazonian palms ( Astrocaryum vulgare Mart., Oenocarpus distichus Mart.) and co-occurring trees. Palms demonstrated substantially higher absolute water storage capacity and greater seasonal and diurnal water mobilisation compared to dicots. Using a novel analysis for critical relative stem water content thresholds revealed striking physiological divergence: palms maintained high relative diurnal discharge capacity, (i.e., the amount of water that can be released from the stem during the day, relative to the maximum capacity), at hydration levels where dicots exhibited significant impairment. In addition, we identify a common soil moisture threshold at 0.19 m 3 m −3 below which stem water declines rapidly, indicating likely hydraulic disconnection from the soil. We demonstrate the usefulness of FDR technology combined with a new threshold analysis to describe how tropical palms and trees respond to increasing drought stress under climate change.

Phosphorus and base cations drive contrasting root dynamics in a central Amazon forest - Jéssica Schmeisk-Rosa; Kelly M. Andersen; Amanda L. Cordeiro; Anna Carolina Martins Moraes; Ana Cláudia Francisco Salomão; Rafael Leandro de Assis; Raffaello Di Ponzio; Renata Vilar de Almeida; Maria Pires Martins; Hellen Fernanda Viana Cunha; Nathielly Pires Martins; Sheila Trierveiler de Souza; et al. (Plant and Soil, 2026)
Background and aims In highly weathered soils of central Amazonia, where nutrients such as phosphorus (P) and base cations are scarce, fertilization experiments have demonstrated above- and belowground effects on total net primary productivity (NPP). This study examined how fine root stocks and turnover responded to added nutrients over a two-year period. We predicted that adding a limiting nutrient would decrease fine root stocks and increase turnover, with the strongest effects from P, followed by base cations, and no response to N. Methods Fine roots (< 2 mm diameter) were sampled from the 0–30 cm soil layer in a low-fertility primary forest in central Amazon subjected to a large-scale factorial experiment adding P, base cations, and N over two years. Fine root turnover was calculated as the ratio between fine root productivity, measured with in-growth cores, and fine root stock. Results Fine root stocks remained unchanged with nutrient addition. However, P increased root turnover by 23% and 48% in the first and second years, respectively, while base cations addition reduced turnover by 24% in year two. N had no significant effect, though a trend toward reduced turnover was observed in the second year. Conclusion The results of this study show that fine root standing stock and turnover in the central Amazon are regulated by soil nutrient availability, especially P and base cations. The contrasting responses observed suggest distinct belowground resource-use strategies for different nutrients, shaped by the nutrient specific mobility in the soil and physiological role in the plant.

Microbial death in the Andes: necromass declines despite growth and carbon-use-efficiency increases with decadal soil warming - Andrew T. Nottingham; Kristiina Karhu; Norma Salinas; Jörg Schnecker; Outi-Maaria Sietiö; Angela K. Martin-Vivanco; Wolfgang Wanek; Patrick Meir (Soil Biology and Biochemistry, 2026)

Tropical Montane Cloud Forests Have High Resilience to Five Years of Severe Soil Drought - David C. Bartholomew; Paulo R. L. Bittencourt; Darcy Galiano Cabrera; Roxana Sacatuma Cruz; Jimmy R. Chambi Paucar; Daniela Corrales Alvarez; Eric Cosio; Blanca Espinoza Otazu; Darwin Manuel Mamani; Patrick Meir; George A. Muñoz Hermoza; Rafael S. Oliveira; et al. (Global Change Biology, 2026)
Tropical montane cloud forests (TMCFs) are globally important ecosystems, acting as large carbon sinks and supporting exceptional biodiversity. However, climate‐driven declines in rainfall threaten these forests, but their responses to long‐term soil moisture deficit remain poorly understood. We implemented a 5‐year throughfall exclusion (TFE) experiment in a Peruvian TMCF, reducing soil moisture by 69.1% across a 0.09 ha plot. We compared the full carbon cycle budget, and surveyed tree physiological traits linked to hydraulics, metabolism and nutrients in the TFE plot and an adjacent, unmodified control (CON) plot. Soil drought reduced gross primary productivity by 4.24 ± 1.97 Mg C ha −1 year −1 but did not change net primary productivity because of an equivalent 3.38 ± 1.42 Mg C ha −1 year −1 decline in autotrophic respiration. Net ecosystem exchange also remained unchanged over 5 years of soil drought. Trees did not change xylem conductivity, hydraulic safety margins or photosynthetic capacity in the TFE, but did have 0.027 ± 0.011 g cm −3 denser wood and 4.58% ± 1.03% higher trunk starch concentrations. These results suggest that trees in TMCF avoid hydraulic failure and carbon starvation under sustained soil moisture drought via metabolic downregulation, resource conservation and non‐structural carbohydrate storage. However, reduced uptake of nutrients (nitrogen, phosphorus, calcium) and 90.6% ± 29.8% decline in fruit production may impact future growth and demography. Our findings demonstrate surprising resilience of TMCFs to sustained, severe soil drought but highlight potential impacts on nutrient cycling and reproduction under climate change. Understanding the impacts of soil drought in conjunction with other climatic changes (e.g., fog reduction, temperature increases) is needed to fully assess the resilience of TMCFs to climate change.

Amazonian trees functional adjustments to long term experimental drought are limited and species dependent - Vanessa Negrão-Rodrigues; Paulo Bittencourt; Pablo Sanchez-Martinez; Lucy Rowland; Lion R. Martius; Patrick Meir; Manolo T. Quintilhan; José Roberto V. Aragão; Victor Brigatto; Vinicius D. Oliveira; Peter Groenendijk; Arlete A. Soares; et al. (Flora, 2025)

Realistic virtual forests for understanding forest disturbances and recovery from space - Kim Calders; Martin Herold; Jennifer Adams; John Armston; Benjamin Brede; Wout Cherlet; Zane T. Cooper; Karun Dayal; Pieter De Frenne; Shaun R. Levick; Patrick Meir; Niall Origo; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Unexpected Large Photosynthetic Thermal Plasticity of Montane Andean Trees - Mirindi Eric Dusenge; Sebastian González‐Caro; Zorayda Restrepo; Anna Gardner; Patrick Meir; Iain P. Hartley; Stephen Sitch; Adriana Sanchez; Juan Camilo Villegas; Lina M. Mercado (Global Change Biology, 2025)
Tropical forests play a significant role in global carbon sequestration. However, our understanding of how tropical tree species adjust to climate warming remains limited to studies on seedlings grown in pots and highly controlled growth conditions. To reduce this knowledge gap, we used a field experiment with 5‐year‐old juvenile trees of 12 naturally co‐occurring dominant tropical Andean montane and lowland species growing in three common gardens established along a natural thermosequence in the tropical Andes. Based on a few previous studies, we hypothesized that montane species would exhibit a weaker photosynthetic thermal acclimation capacity compared to lowland counterparts. Our results showed that montane tree species can thermally acclimate net photosynthesis by shifting their thermal optimum ( T opt ) by 0.6°C per 1°C of warming. This strong shift in T opt was correlated to simultaneous strong shifts in T opt of apparent photosynthetic capacity parameters ( V cmax and J max ), which increased by 0.7°C per 1°C of warming. This strong thermal acclimation resulted in similar rates of net CO 2 assimilation between montane and lowland species across different thermal environments. At last, rates of net photosynthesis at growth temperature explained 30% of the variation in the relative tree growth rates across the two species groups and thermal environments. Our results suggest that the strong physiological acclimation of photosynthesis to warming among montane Andean tree species should be considered when predicting future impacts of warming on Andean plant communities.

A Theoretical Framework to Quantify Ecosystem Pressure‐Volume Relationships - Oliver Binks; Patrick Meir; Alexandra G. Konings; Lucas Cernusak; Bradley O. Christoffersen; William R. L. Anderegg; Jeffrey Wood; Lawren Sack; Jordi Martinez‐Vilalta; Maurizio Mencuccini (Global Change Biology, 2024)
‘Water potential’ is the biophysically relevant measure of water status in vegetation relating to stomatal, canopy and hydraulic conductance, as well as mortality thresholds; yet, this cannot be directly related to measured and modelled fluxes of water at plot‐ to landscape‐scale without understanding its relationship with ‘water content’. The capacity for detecting vegetation water content via microwave remote sensing further increases the need to understand the link between water content and ecosystem function. In this review, we explore how the fundamental measures of water status, water potential and water content are linked at ecosystem‐scale drawing on the existing theory of pressure‐volume (PV) relationships. We define and evaluate the concept and limitations of applying PV relationships to ecosystems where the quantity of water can vary on short timescales with respect to plant water status, and over longer timescales and over larger areas due to structural changes in vegetation. As a proof of concept, plot‐scale aboveground vegetation PV curves were generated from equilibrium (e.g., predawn) water potentials and water content of the above ground biomass of nine plots, including tropical rainforest, savanna, temperate forest, and a long‐term Amazonian rainforest drought experiment. Initial findings suggest that the stored water and ecosystem capacitance scale linearly with biomass across diverse systems, while the relative values of ecosystem hydraulic capacitance and physiologically accessible water storage do not vary systematically with biomass. The bottom‐up scaling approach to ecosystem water relations identified the need to characterise the distribution of water potentials within a community and also revealed the relevance of community‐level plant tissue fractions to ecosystem water relations. We believe that this theory will be instrumental in linking our detailed understanding of biophysical processes at tissue‐scale to the scale at which land surface models operate and at which tower‐based, airborne and satellite remote sensing can provide information.

New tree height allometries derived from terrestrial laser scanning reveal substantial discrepancies with forest inventory methods in tropical rainforests - Louise Terryn; Kim Calders; Félicien Meunier; Marijn Bauters; Pascal Boeckx; Benjamin Brede; Andrew Burt; Jerome Chave; Antonio Carlos Lola da Costa; Barbara D'hont; Mathias Disney; Tommaso Jucker; et al. (Global Change Biology, 2024)
Tree allometric models, essential for monitoring and predicting terrestrial carbon stocks, are traditionally built on global databases with forest inventory measurements of stem diameter (D) and tree height (H). However, these databases often combine H measurements obtained through various measurement methods, each with distinct error patterns, affecting the resulting H:D allometries. In recent decades, terrestrial laser scanning (TLS) has emerged as a widely accepted method for accurate, non‐destructive tree structural measurements. This study used TLS data to evaluate the prediction accuracy of forest inventory‐based H:D allometries and to develop more accurate pantropical allometries. We considered 19 tropical rainforest plots across four continents. Eleven plots had forest inventory and RIEGL VZ‐400(i) TLS‐based D and H data, allowing accuracy assessment of local forest inventory‐based H:D allometries. Additionally, TLS‐based data from 1951 trees from all 19 plots were used to create new pantropical H:D allometries for tropical rainforests. Our findings reveal that in most plots, forest inventory‐based H:D allometries underestimated H compared with TLS‐based allometries. For 30‐metre‐tall trees, these underestimations varied from −1.6 m (−5.3%) to −7.5 m (−25.4%). In the Malaysian plot with trees reaching up to 77 m in height, the underestimation was as much as −31.7 m (−41.3%). We propose a TLS‐based pantropical H:D allometry, incorporating maximum climatological water deficit for site effects, with a mean uncertainty of 19.1% and a mean bias of −4.8%. While the mean uncertainty is roughly 2.3% greater than that of the Chave2014 model, this model demonstrates more consistent uncertainties across tree size and delivers less biased estimates of H (with a reduction of 8.23%). In summary, recognizing the errors in H measurements from forest inventory methods is vital, as they can propagate into the allometries they inform. This study underscores the potential of TLS for accurate H and D measurements in tropical rainforests, essential for refining tree allometries.

Networking the forest infrastructure towards near real-time monitoring – A white paper - Roman Zweifel; Christoforos Pappas; Richard L. Peters; Flurin Babst; Daniel Balanzategui; David Basler; Ana Bastos; Mirela Beloiu; Nina Buchmann; Arun K. Bose; Sabine Braun; Alexander Damm; et al. (Science of The Total Environment, 2023)

Induced drought strongly affects richness and composition of ground-dwelling ants in the eastern Amazon - Rony P. S. Almeida; Rogério R. Silva; Antonio C. Lôla da Costa; Leandro V. Ferreira; Patrick Meir; Aaron M. Ellison (Oecologia, 2023)

No evidence of positive feedback between litter deposition and seedling growth rate in Neotropical savannas - André M. D’Angioli; Vinicius L. Dantas; Marcio Lambais; Patrick Meir; Rafael S. Oliveira (Plant and Soil, 2021)

Detecting forest response to droughts with global observations of vegetation water content - Alexandra G. Konings; Sassan S. Saatchi; Christian Frankenberg; Michael Keller; Victor Leshyk; William R. L. Anderegg; Vincent Humphrey; Ashley M. Matheny; Anna Trugman; Lawren Sack; Elizabeth Agee; Mallory L. Barnes; et al. (Global Change Biology, 2021)
Droughts in a warming climate have become more common and more extreme, making understanding forest responses to water stress increasingly pressing. Analysis of water stress in trees has long focused on water potential in xylem and leaves, which influences stomatal closure and water flow through the soil‐plant‐atmosphere continuum. At the same time, changes of vegetation water content (VWC) are linked to a range of tree responses, including fluxes of water and carbon, mortality, flammability, and more. Unlike water potential, which requires demanding in situ measurements, VWC can be retrieved from remote sensing measurements, particularly at microwave frequencies using radar and radiometry. Here, we highlight key frontiers through which VWC has the potential to significantly increase our understanding of forest responses to water stress. To validate remote sensing observations of VWC at landscape scale and to better relate them to data assimilation model parameters, we introduce an ecosystem‐scale analog of the pressure–volume curve, the non‐linear relationship between average leaf or branch water potential and water content commonly used in plant hydraulics. The sources of variability in these ecosystem‐scale pressure‐volume curves and their relationship to forest response to water stress are discussed. We further show to what extent diel, seasonal, and decadal dynamics of VWC reflect variations in different processes relating the tree response to water stress. VWC can also be used for inferring belowground conditions—which are difficult to impossible to observe directly. Lastly, we discuss how a dedicated geostationary spaceborne observational system for VWC, when combined with existing datasets, can capture diel and seasonal water dynamics to advance the science and applications of global forest vulnerability to future droughts.

Fine root dynamics across pantropical rainforest ecosystems - Walter Huaraca Huasco; Terhi Riutta; Cécile A. J. Girardin; Fernando Hancco Pacha; Beisit L. Puma Vilca; Sam Moore; Sami W. Rifai; Jhon del Aguila‐Pasquel; Alejandro Araujo Murakami; Renata Freitag; Alexandra C. Morel; Sheleme Demissie; et al. (Global Change Biology, 2021)
Fine roots constitute a significant component of the net primary productivity (NPP) of forest ecosystems but are much less studied than aboveground NPP. Comparisons across sites and regions are also hampered by inconsistent methodologies, especially in tropical areas. Here, we present a novel dataset of fine root biomass, productivity, residence time, and allocation in tropical old‐growth rainforest sites worldwide, measured using consistent methods, and examine how these variables are related to consistently determined soil and climatic characteristics. Our pantropical dataset spans intensive monitoring plots in lowland (wet, semi‐deciduous, and deciduous) and montane tropical forests in South America, Africa, and Southeast Asia ( n = 47). Large spatial variation in fine root dynamics was observed across montane and lowland forest types. In lowland forests, we found a strong positive linear relationship between fine root productivity and sand content, this relationship was even stronger when we considered the fractional allocation of total NPP to fine roots, demonstrating that understanding allocation adds explanatory power to understanding fine root productivity and total NPP. Fine root residence time was a function of multiple factors: soil sand content, soil pH, and maximum water deficit, with longest residence times in acidic, sandy, and water‐stressed soils. In tropical montane forests, on the other hand, a different set of relationships prevailed, highlighting the very different nature of montane and lowland forest biomes. Root productivity was a strong positive linear function of mean annual temperature, root residence time was a strong positive function of soil nitrogen content in montane forests, and lastly decreasing soil P content increased allocation of productivity to fine roots. In contrast to the lowlands, environmental conditions were a better predictor for fine root productivity than for fractional allocation of total NPP to fine roots, suggesting that root productivity is a particularly strong driver of NPP allocation in tropical mountain regions.

Does economic optimisation explain LAI and leaf trait distributions across an Amazon soil moisture gradient? - Sophie Flack‐Prain; Patrick Meir; Yadvinder Malhi; Thomas L. Smallman; Mathew Williams (Global Change Biology, 2021)
Leaf area index (LAI) underpins terrestrial ecosystem functioning, yet our ability to predict LAI remains limited. Across Amazon forests, mean LAI, LAI seasonal dynamics and leaf traits vary with soil moisture stress. We hypothesise that LAI variation can be predicted via an optimality‐based approach, using net canopy C export (NCE, photosynthesis minus the C cost of leaf growth and maintenance) as a fitness proxy. We applied a process‐based terrestrial ecosystem model to seven plots across a moisture stress gradient with detailed in situ measurements, to determine nominal plant C budgets. For each plot, we then compared observations and simulations of the nominal (i.e. observed) C budget to simulations of alternative, experimental budgets. Experimental budgets were generated by forcing the model with synthetic LAI timeseries (across a range of mean LAI and LAI seasonality) and different leaf trait combinations (leaf mass per unit area, lifespan, photosynthetic capacity and respiration rate) operating along the leaf economic spectrum. Observed mean LAI and LAI seasonality across the soil moisture stress gradient maximised NCE, and were therefore consistent with optimality‐based predictions. Yet, the predictive power of an optimality‐based approach was limited due to the asymptotic response of simulated NCE to mean LAI and LAI seasonality. Leaf traits fundamentally shaped the C budget, determining simulated optimal LAI and total NCE. Long‐lived leaves with lower maximum photosynthetic capacity maximised simulated NCE under aseasonal high mean LAI, with the reverse found for short‐lived leaves and higher maximum photosynthetic capacity. The simulated leaf trait LAI trade‐offs were consistent with observed distributions. We suggest that a range of LAI strategies could be equally economically viable at local level, though we note several ecological limitations to this interpretation (e.g. between‐plant competition). In addition, we show how leaf trait trade‐offs enable divergence in canopy strategies. Our results also allow an assessment of the usefulness of optimality‐based approaches in simulating primary tropical forest functioning, evaluated against in situ data.

Identifying areas at risk of drought‐induced tree mortality across South‐Eastern Australia - Martin G. De Kauwe; Belinda E. Medlyn; Anna M. Ukkola; Mengyuan Mu; Manon E. B. Sabot; Andrew J. Pitman; Patrick Meir; Lucas A. Cernusak; Sami W. Rifai; Brendan Choat; David T. Tissue; Chris J. Blackman; et al. (Global Change Biology, 2020)
South‐East Australia has recently been subjected to two of the worst droughts in the historical record (Millennium Drought, 2000–2009 and Big Dry, 2017–2019). Unfortunately, a lack of forest monitoring has made it difficult to determine whether widespread tree mortality has resulted from these droughts. Anecdotal observations suggest the Big Dry may have led to more significant tree mortality than the Millennium drought. Critically, to be able to robustly project future expected climate change effects on Australian vegetation, we need to assess the vulnerability of Australian trees to drought. Here we implemented a model of plant hydraulics into the Community Atmosphere Biosphere Land Exchange (CABLE) land surface model. We parameterized the drought response behaviour of five broad vegetation types, based on a common garden dry‐down experiment with species originating across a rainfall gradient (188–1,125 mm/year) across South‐East Australia. The new hydraulics model significantly improved (~35%–45% reduction in root mean square error) CABLE’s previous predictions of latent heat fluxes during periods of water stress at two eddy covariance sites in Australia. Landscape‐scale predictions of the greatest percentage loss of hydraulic conductivity (PLC) of about 40%–60%, were broadly consistent with satellite estimates of regions of the greatest change in both droughts. In neither drought did CABLE predict that trees would have reached critical PLC in widespread areas (i.e. it projected a low mortality risk), although the model highlighted critical levels near the desert regions of South‐East Australia where few trees live. Overall, our experimentally constrained model results imply significant resilience to drought conferred by hydraulic function, but also highlight critical data and scientific gaps. Our approach presents a promising avenue to integrate experimental data and make regional‐scale predictions of potential drought‐induced hydraulic failure.

Rainfall manipulation experiments as simulated by terrestrial biosphere models: Where do we stand? - Athanasios Paschalis; Simone Fatichi; Jakob Zscheischler; Philippe Ciais; Michael Bahn; Lena Boysen; Jinfeng Chang; Martin De Kauwe; Marc Estiarte; Daniel Goll; Paul J. Hanson; Anna B. Harper; et al. (Global Change Biology, 2020)
Changes in rainfall amounts and patterns have been observed and are expected to continue in the near future with potentially significant ecological and societal consequences. Modelling vegetation responses to changes in rainfall is thus crucial to project water and carbon cycles in the future. In this study, we present the results of a new model‐data intercomparison project, where we tested the ability of 10 terrestrial biosphere models to reproduce the observed sensitivity of ecosystem productivity to rainfall changes at 10 sites across the globe, in nine of which, rainfall exclusion and/or irrigation experiments had been performed. The key results are as follows: (a) Inter‐model variation is generally large and model agreement varies with timescales. In severely water‐limited sites, models only agree on the interannual variability of evapotranspiration and to a smaller extent on gross primary productivity. In more mesic sites, model agreement for both water and carbon fluxes is typically higher on fine (daily–monthly) timescales and reduces on longer (seasonal–annual) scales. (b) Models on average overestimate the relationship between ecosystem productivity and mean rainfall amounts across sites (in space) and have a low capacity in reproducing the temporal (interannual) sensitivity of vegetation productivity to annual rainfall at a given site, even though observation uncertainty is comparable to inter‐model variability. (c) Most models reproduced the sign of the observed patterns in productivity changes in rainfall manipulation experiments but had a low capacity in reproducing the observed magnitude of productivity changes. Models better reproduced the observed productivity responses due to rainfall exclusion than addition. (d) All models attribute ecosystem productivity changes to the intensity of vegetation stress and peak leaf area, whereas the impact of the change in growing season length is negligible. The relative contribution of the peak leaf area and vegetation stress intensity was highly variable among models.

Amazonia trees have limited capacity to acclimate plant hydraulic properties in response to long‐term drought - Paulo R. L. Bittencourt; Rafael S. Oliveira; Antonio C. L. da Costa; Andre L. Giles; Ingrid Coughlin; Patricia B. Costa; David C. Bartholomew; Leandro V. Ferreira; Steel S. Vasconcelos; Fernanda V. Barros; Joao A. S. Junior; Alex A. R. Oliveira; et al. (Global Change Biology, 2020)
The fate of tropical forests under future climate change is dependent on the capacity of their trees to adjust to drier conditions. The capacity of trees to withstand drought is likely to be determined by traits associated with their hydraulic systems. However, data on whether tropical trees can adjust hydraulic traits when experiencing drought remain rare. We measured plant hydraulic traits (e.g. hydraulic conductivity and embolism resistance) and plant hydraulic system status (e.g. leaf water potential, native embolism and safety margin) on >150 trees from 12 genera (36 species) and spanning a stem size range from 14 to 68 cm diameter at breast height at the world's only long‐running tropical forest drought experiment. Hydraulic traits showed no adjustment following 15 years of experimentally imposed moisture deficit. This failure to adjust resulted in these drought‐stressed trees experiencing significantly lower leaf water potentials, and higher, but variable, levels of native embolism in the branches. This result suggests that hydraulic damage caused by elevated levels of embolism is likely to be one of the key drivers of drought‐induced mortality following long‐term soil moisture deficit. We demonstrate that some hydraulic traits changed with tree size, however, the direction and magnitude of the change was controlled by taxonomic identity. Our results suggest that Amazonian trees, both small and large, have limited capacity to acclimate their hydraulic systems to future droughts, potentially making them more at risk of drought‐induced mortality.

Multiple phosphorus acquisition strategies adopted by fine roots in low-fertility soils in Central Amazonia - Laynara F. Lugli; Kelly M. Andersen; Luiz E. O. C. Aragão; Amanda L. Cordeiro; Hellen F. V. Cunha; Lucia Fuchslueger; Patrick Meir; Lina M. Mercado; Erick Oblitas; Carlos A. Quesada; Jessica S. Rosa; Karst J. Schaap; et al. (Plant and Soil, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Microbial responses to warming enhance soil carbon loss following translocation across a tropical forest elevation gradient - Andrew T. Nottingham; Jeanette Whitaker; Nick J. Ostle; Richard D. Bardgett; Niall P. McNamara; Noah Fierer; Norma Salinas; Adan J. Q. Ccahuana; Benjamin L. Turner; Patrick Meir (Ecology Letters, 2019)
Tropical soils contain huge carbon stocks, which climate warming is projected to reduce by stimulating organic matter decomposition, creating a positive feedback that will promote further warming. Models predict that the loss of carbon from warming soils will be mediated by microbial physiology, but no empirical data are available on the response of soil carbon and microbial physiology to warming in tropical forests, which dominate the terrestrial carbon cycle. Here we show that warming caused a considerable loss of soil carbon that was enhanced by associated changes in microbial physiology. By translocating soils across a 3000 m elevation gradient in tropical forest, equivalent to a temperature change of ± 15 °C, we found that soil carbon declined over 5 years by 4% in response to each 1 °C increase in temperature. The total loss of carbon was related to its original quantity and lability, and was enhanced by changes in microbial physiology including increased microbial carbon‐use‐efficiency, shifts in community composition towards microbial taxa associated with warmer temperatures, and increased activity of hydrolytic enzymes. These findings suggest that microbial feedbacks will cause considerable loss of carbon from tropical forest soils in response to predicted climatic warming this century.

Foliar water uptake in Amazonian trees: Evidence and consequences - Oliver Binks; Maurizio Mencuccini; Lucy Rowland; Antonio C. L. da Costa; Claudio José Reis de Carvalho; Paulo Bittencourt; Cleiton Eller; Grazielle Sales Teodoro; Eduardo Jorge Maklouf Carvalho; Azul Soza; Leandro Ferreira; Steel Silva Vasconcelos; et al. (Global Change Biology, 2019)
The absorption of atmospheric water directly into leaves enables plants to alleviate the water stress caused by low soil moisture, hydraulic resistance in the xylem and the effect of gravity on the water column, while enabling plants to scavenge small inputs of water from leaf‐wetting events. By increasing the availability of water, and supplying it from the top of the canopy (in a direction facilitated by gravity), foliar uptake (FU) may be a significant process in determining how forests interact with climate, and could alter our interpretation of current metrics for hydraulic stress and sensitivity. FU has not been reported for lowland tropical rainforests; we test whether FU occurs in six common Amazonian tree genera in lowland Amazônia, and make a first estimation of its contribution to canopy–atmosphere water exchange. We demonstrate that FU occurs in all six genera and that dew‐derived water may therefore be used to “pay” for some morning transpiration in the dry season. Using meteorological and canopy wetness data, coupled with empirically derived estimates of leaf conductance to FU ( k fu ), we estimate that the contribution by FU to annual transpiration at this site has a median value of 8.2% (103 mm/year) and an interquartile range of 3.4%–15.3%, with the biggest sources of uncertainty being k fu and the proportion of time the canopy is wet. Our results indicate that FU is likely to be a common strategy and may have significant implications for the Amazon carbon budget. The process of foliar water uptake may also have a profound impact on the drought tolerance of individual Amazonian trees and tree species, and on the cycling of water and carbon, regionally and globally.

Adaptation of soil microbial growth to temperature: Using a tropical elevation gradient to predict future changes - Andrew T. Nottingham; Erland Bååth; Stephanie Reischke; Norma Salinas; Patrick Meir (Global Change Biology, 2019)
Terrestrial biogeochemical feedbacks to the climate are strongly modulated by the temperature response of soil microorganisms. Tropical forests, in particular, exert a major influence on global climate because they are the most productive terrestrial ecosystem. We used an elevation gradient across tropical forest in the Andes (a gradient of 20°C mean annual temperature, MAT), to test whether soil bacterial and fungal community growth responses are adapted to long‐term temperature differences. We evaluated the temperature dependency of soil bacterial and fungal growth using the leucine‐ and acetate‐incorporation methods, respectively, and determined indices for the temperature response of growth: Q 10 (temperature sensitivity over a given 10oC range) and T min (the minimum temperature for growth). For both bacterial and fungal communities, increased MAT (decreased elevation) resulted in increases in Q 10 and T min of growth. Across a MAT range from 6°C to 26°C, the Q 10 and T min varied for bacterial growth ( Q 10–20 = 2.4 to 3.5; T min = −8°C to −1.5°C) and fungal growth ( Q 10–20 = 2.6 to 3.6; T min = −6°C to −1°C). Thus, bacteria and fungi did not differ significantly in their growth temperature responses with changes in MAT. Our findings indicate that across natural temperature gradients, each increase in MAT by 1°C results in increases in T min of microbial growth by approximately 0.3°C and Q 10–20 by 0.05, consistent with long‐term temperature adaptation of soil microbial communities. A 2°C warming would increase microbial activity across a MAT gradient of 6°C to 26°C by 28% to 15%, respectively, and temperature adaptation of microbial communities would further increase activity by 1.2% to 0.3%. The impact of warming on microbial activity, and the related impact on soil carbon cycling, is thus greater in regions with lower MAT. These results can be used to predict future changes in the temperature response of microbial activity over different levels of warming and over large temperature ranges, extending to tropical regions.

Microbes follow Humboldt: temperature drives plant and soil microbial diversity patterns from the Amazon to the Andes - Andrew T. Nottingham; Noah Fierer; Benjamin L. Turner; Jeanette Whitaker; Nick J. Ostle; Niall P. McNamara; Richard D. Bardgett; Jonathan W. Leff; Norma Salinas; Miles R. Silman; Loeske E. B. Kruuk; Patrick Meir (Ecology, 2018)
More than 200 years ago, Alexander von Humboldt reported that tropical plant species richness decreased with increasing elevation and decreasing temperature. Surprisingly, coordinated patterns in plant, bacterial, and fungal diversity on tropical mountains have not yet been observed, despite the central role of soil microorganisms in terrestrial biogeochemistry and ecology. We studied an Andean transect traversing 3.5 km in elevation to test whether the species diversity and composition of tropical forest plants, soil bacteria, and fungi follow similar biogeographical patterns with shared environmental drivers. We found coordinated changes with elevation in all three groups: species richness declined as elevation increased, and the compositional dissimilarity among communities increased with increased separation in elevation, although changes in plant diversity were larger than in bacteria and fungi. Temperature was the dominant driver of these diversity gradients, with weak influences of edaphic properties, including soil pH . The gradients in microbial diversity were strongly correlated with the activities of enzymes involved in organic matter cycling, and were accompanied by a transition in microbial traits towards slower‐growing, oligotrophic taxa at higher elevations. We provide the first evidence of coordinated temperature‐driven patterns in the diversity and distribution of three major biotic groups in tropical ecosystems: soil bacteria, fungi, and plants. These findings suggest that interrelated and fundamental patterns of plant and microbial communities with shared environmental drivers occur across landscape scales. These patterns are revealed where soil pH is relatively constant, and have implications for tropical forest communities under future climate change.

Nutrient limitations to bacterial and fungal growth during cellulose decomposition in tropical forest soils - Andrew T. Nottingham; Lettice C. Hicks; Adan J. Q. Ccahuana; Norma Salinas; Erland Bååth; Patrick Meir (Biology and Fertility of Soils, 2018)

Stand dynamics modulate water cycling and mortality risk in droughted tropical forest - Antonio C. L. da Costa; Lucy Rowland; Rafael S. Oliveira; Alex A. R. Oliveira; Oliver J. Binks; Yann Salmon; Steel S. Vasconcelos; João A. S. Junior; Leandro V. Ferreira; Rafael Poyatos; Maurizio Mencuccini; Patrick Meir (Global Change Biology, 2018)
Transpiration from the Amazon rainforest generates an essential water source at a global and local scale. However, changes in rainforest function with climate change can disrupt this process, causing significant reductions in precipitation across Amazonia, and potentially at a global scale. We report the only study of forest transpiration following a long‐term (>10 year) experimental drought treatment in Amazonian forest. After 15 years of receiving half the normal rainfall, drought‐related tree mortality caused total forest transpiration to decrease by 30%. However, the surviving droughted trees maintained or increased transpiration because of reduced competition for water and increased light availability, which is consistent with increased growth rates. Consequently, the amount of water supplied as rainfall reaching the soil and directly recycled as transpiration increased to 100%. This value was 25% greater than for adjacent nondroughted forest. If these drought conditions were accompanied by a modest increase in temperature (e.g., 1.5°C), water demand would exceed supply, making the forest more prone to increased tree mortality.

Differences in xylem and leaf hydraulic traits explain differences in drought tolerance among mature Amazon rainforest trees - Thomas L. Powell; James K. Wheeler; Alex A. R. de Oliveira; Antonio Carlos Lola da Costa; Scott R. Saleska; Patrick Meir; Paul R. Moorcroft (Global Change Biology, 2017)
Considerable uncertainty surrounds the impacts of anthropogenic climate change on the composition and structure of Amazon forests. Building upon results from two large‐scale ecosystem drought experiments in the eastern Brazilian Amazon that observed increases in mortality rates among some tree species but not others, in this study we investigate the physiological traits underpinning these differential demographic responses. Xylem pressure at 50% conductivity (xylem‐P 50 ), leaf turgor loss point ( TLP ), cellular osmotic potential (π o ), and cellular bulk modulus of elasticity (ε), all traits mechanistically linked to drought tolerance, were measured on upper canopy branches and leaves of mature trees from selected species growing at the two drought experiment sites. Each species was placed a priori into one of four plant functional type ( PFT ) categories: drought‐tolerant versus drought‐intolerant based on observed mortality rates, and subdivided into early‐ versus late‐successional based on wood density. We tested the hypotheses that the measured traits would be significantly different between the four PFT s and that they would be spatially conserved across the two experimental sites. Xylem‐P 50 , TLP , and π o , but not ε, occurred at significantly higher water potentials for the drought‐intolerant PFT compared to the drought‐tolerant PFT ; however, there were no significant differences between the early‐ and late‐successional PFT s. These results suggest that these three traits are important for determining drought tolerance, and are largely independent of wood density—a trait commonly associated with successional status. Differences in these physiological traits that occurred between the drought‐tolerant and drought‐intolerant PFT s were conserved between the two research sites, even though they had different soil types and dry‐season lengths. This more detailed understanding of how xylem and leaf hydraulic traits vary between co‐occuring drought‐tolerant and drought‐intolerant tropical tree species promises to facilitate a much‐needed improvement in the representation of plant hydraulics within terrestrial ecosystem and biosphere models, which will enhance our ability to make robust predictions of how future changes in climate will affect tropical forests.

Solar radiation and functional traits explain the decline of forest primary productivity along a tropical elevation gradient - Nikolaos M. Fyllas; Lisa Patrick Bentley; Alexander Shenkin; Gregory P. Asner; Owen K. Atkin; Sandra Díaz; Brian J. Enquist; William Farfan‐Rios; Emanuel Gloor; Rossella Guerrieri; Walter Huaraca Huasco; Yoko Ishida; et al. (Ecology Letters, 2017)
One of the major challenges in ecology is to understand how ecosystems respond to changes in environmental conditions, and how taxonomic and functional diversity mediate these changes. In this study, we use a trait‐spectra and individual‐based model, to analyse variation in forest primary productivity along a 3.3 km elevation gradient in the Amazon‐Andes. The model accurately predicted the magnitude and trends in forest productivity with elevation, with solar radiation and plant functional traits (leaf dry mass per area, leaf nitrogen and phosphorus concentration, and wood density) collectively accounting for productivity variation. Remarkably, explicit representation of temperature variation with elevation was not required to achieve accurate predictions of forest productivity, as trait variation driven by species turnover appears to capture the effect of temperature. Our semi‐mechanistic model suggests that spatial variation in traits can potentially be used to estimate spatial variation in productivity at the landscape scale.

Thermal limits of leaf metabolism across biomes - Odhran S. O'sullivan; Mary A. Heskel; Peter B. Reich; Mark G. Tjoelker; Lasantha K. Weerasinghe; Aurore Penillard; Lingling Zhu; John J. G. Egerton; Keith J. Bloomfield; Danielle Creek; Nur H. A. Bahar; Kevin L. Griffin; et al. (Global Change Biology, 2017)
High‐temperature tolerance in plants is important in a warming world, with extreme heat waves predicted to increase in frequency and duration, potentially leading to lethal heating of leaves. Global patterns of high‐temperature tolerance are documented in animals, but generally not in plants, limiting our ability to assess risks associated with climate warming. To assess whether there are global patterns in high‐temperature tolerance of leaf metabolism, we quantified T crit (high temperature where minimal chlorophyll a fluorescence rises rapidly and thus photosystem II is disrupted) and T max (temperature where leaf respiration in darkness is maximal, beyond which respiratory function rapidly declines) in upper canopy leaves of 218 plant species spanning seven biomes. Mean site‐based T crit values ranged from 41.5 °C in the Alaskan arctic to 50.8 °C in lowland tropical rainforests of Peruvian Amazon. For T max , the equivalent values were 51.0 and 60.6 °C in the Arctic and Amazon, respectively. T crit and T max followed similar biogeographic patterns, increasing linearly ( ˜ 8 °C) from polar to equatorial regions. Such increases in high‐temperature tolerance are much less than expected based on the 20 °C span in high‐temperature extremes across the globe. Moreover, with only modest high‐temperature tolerance despite high summer temperature extremes, species in mid‐latitude (~20–50°) regions have the narrowest thermal safety margins in upper canopy leaves; these regions are at the greatest risk of damage due to extreme heat‐wave events, especially under conditions when leaf temperatures are further elevated by a lack of transpirational cooling. Using predicted heat‐wave events for 2050 and accounting for possible thermal acclimation of T crit and T max , we also found that these safety margins could shrink in a warmer world, as rising temperatures are likely to exceed thermal tolerance limits. Thus, increasing numbers of species in many biomes may be at risk as heat‐wave events become more severe with climate change.

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

After more than a decade of soil moisture deficit, tropical rainforest trees maintain photosynthetic capacity, despite increased leaf respiration - Lucy Rowland; Raquel L. Lobo‐do‐Vale; Bradley O. Christoffersen; Eliane A. Melém; Bart Kruijt; Steel S. Vasconcelos; Tomas Domingues; Oliver J. Binks; Alex A. R. Oliveira; Daniel Metcalfe; Antonio C. L. da Costa; Maurizio Mencuccini; et al. (Global Change Biology, 2015)
Determining climate change feedbacks from tropical rainforests requires an understanding of how carbon gain through photosynthesis and loss through respiration will be altered. One of the key changes that tropical rainforests may experience under future climate change scenarios is reduced soil moisture availability. In this study we examine if and how both leaf photosynthesis and leaf dark respiration acclimate following more than 12 years of experimental soil moisture deficit, via a through‐fall exclusion experiment ( TFE ) in an eastern Amazonian rainforest. We find that experimentally drought‐stressed trees and taxa maintain the same maximum leaf photosynthetic capacity as trees in corresponding control forest, independent of their susceptibility to drought‐induced mortality. We hypothesize that photosynthetic capacity is maintained across all treatments and taxa to take advantage of short‐lived periods of high moisture availability, when stomatal conductance ( g s ) and photosynthesis can increase rapidly, potentially compensating for reduced assimilate supply at other times. Average leaf dark respiration ( R d ) was elevated in the TFE ‐treated forest trees relative to the control by 28.2 ± 2.8% (mean ± one standard error). This mean R d value was dominated by a 48.5 ± 3.6% increase in the R d of drought‐sensitive taxa, and likely reflects the need for additional metabolic support required for stress‐related repair, and hydraulic or osmotic maintenance processes. Following soil moisture deficit that is maintained for several years, our data suggest that changes in respiration drive greater shifts in the canopy carbon balance, than changes in photosynthetic capacity.

Biome-specific effects of nitrogen and phosphorus on the photosynthetic characteristics of trees at a forest-savanna boundary in Cameroon - Tomas Ferreira Domingues; F. Yoko Ishida; Ted R. Feldpausch; John Grace; Patrick Meir; Gustavo Saiz; Olivier Sene; Franziska Schrodt; Bonaventure Sonké; Herman Taedoumg; Elmar M. Veenendaal; Simon Lewis; et al. (Oecologia, 2015)

The linkages between photosynthesis, productivity, growth and biomass in lowland Amazonian forests - Yadvinder Malhi; Christopher E. Doughty; Gregory R. Goldsmith; Daniel B. Metcalfe; Cécile A. J. Girardin; Toby R. Marthews; Jhon del Aguila‐Pasquel; Luiz E. O. C. Aragão; Alejandro Araujo‐Murakami; Paulo Brando; Antonio C. L. da Costa; Javier E. Silva‐Espejo; et al. (Global Change Biology, 2015)
Understanding the relationship between photosynthesis, net primary productivity and growth in forest ecosystems is key to understanding how these ecosystems will respond to global anthropogenic change, yet the linkages among these components are rarely explored in detail. We provide the first comprehensive description of the productivity, respiration and carbon allocation of contrasting lowland Amazonian forests spanning gradients in seasonal water deficit and soil fertility. Using the largest data set assembled to date, ten sites in three countries all studied with a standardized methodology, we find that (i) gross primary productivity ( GPP ) has a simple relationship with seasonal water deficit, but that (ii) site‐to‐site variations in GPP have little power in explaining site‐to‐site spatial variations in net primary productivity ( NPP ) or growth because of concomitant changes in carbon use efficiency ( CUE ), and conversely, the woody growth rate of a tropical forest is a very poor proxy for its productivity. Moreover, (iii) spatial patterns of biomass are much more driven by patterns of residence times (i.e. tree mortality rates) than by spatial variation in productivity or tree growth. Current theory and models of tropical forest carbon cycling under projected scenarios of global atmospheric change can benefit from advancing beyond a focus on GPP . By improving our understanding of poorly understood processes such as CUE , NPP allocation and biomass turnover times, we can provide more complete and mechanistic approaches to linking climate and tropical forest carbon cycling.

Markedly divergent estimates of A mazon forest carbon density from ground plots and satellites - Edward T. A. Mitchard; Ted R. Feldpausch; Roel J. W. Brienen; Gabriela Lopez‐Gonzalez; Abel Monteagudo; Timothy R. Baker; Simon L. Lewis; Jon Lloyd; Carlos A. Quesada; Manuel Gloor; Hans ter Steege; Patrick Meir; et al. (Global Ecology and Biogeography, 2014)
Aim The accurate mapping of forest carbon stocks is essential for understanding the global carbon cycle, for assessing emissions from deforestation, and for rational land‐use planning. Remote sensing ( RS ) is currently the key tool for this purpose, but RS does not estimate vegetation biomass directly, and thus may miss significant spatial variations in forest structure. We test the stated accuracy of pantropical carbon maps using a large independent field dataset. Location Tropical forests of the A mazon basin. The permanent archive of the field plot data can be accessed at: http://dx.doi.org/10.5521/FORESTPLOTS.NET/2014_1 Methods Two recent pantropical RS maps of vegetation carbon are compared to a unique ground‐plot dataset, involving tree measurements in 413 large inventory plots located in nine countries. The RS maps were compared directly to field plots, and kriging of the field data was used to allow area‐based comparisons. Results The two RS carbon maps fail to capture the main gradient in Amazon forest carbon detected using 413 ground plots, from the densely wooded tall forests of the north‐east, to the light‐wooded, shorter forests of the south‐west. The differences between plots and RS maps far exceed the uncertainties given in these studies, with whole regions over‐ or under‐estimated by > 25%, whereas regional uncertainties for the maps were reported to be Main conclusions Pantropical biomass maps are widely used by governments and by projects aiming to reduce deforestation using carbon offsets, but may have significant regional biases. Carbon‐mapping techniques must be revised to account for the known ecological variation in tree wood density and allometry to create maps suitable for carbon accounting. The use of single relationships between tree canopy height and above‐ground biomass inevitably yields large, spatially correlated errors. This presents a significant challenge to both the forest conservation and remote sensing communities, because neither wood density nor species assemblages can be reliably mapped from space.

Amazon forest biomass density maps: tackling the uncertainty in carbon emission estimates - Jean Pierre Ometto; Ana Paula Aguiar; Talita Assis; Luciana Soler; Pedro Valle; Graciela Tejada; David M. Lapola; Patrick Meir (Climatic Change, 2014)

Gross Primary Productivity of a High Elevation Tropical Montane Cloud Forest - Martine Janet van de Weg; Patrick Meir; Mat Williams; Cécile Girardin; Yadvinder Malhi; Javier Silva-Espejo; John Grace (Ecosystems, 2014)

Evidence for strong seasonality in the carbon storage and carbon use efficiency of an Amazonian forest - Lucy Rowland; Timothy Charles Hill; Clement Stahl; Lukas Siebicke; Benoit Burban; Joana Zaragoza‐Castells; Stephane Ponton; Damien Bonal; Patrick Meir; Mathew Williams (Global Change Biology, 2014)
The relative contribution of gross primary production and ecosystem respiration to seasonal changes in the net carbon flux of tropical forests remains poorly quantified by both modelling and field studies. We use data assimilation to combine nine ecological time series from an eastern Amazonian forest, with mass balance constraints from an ecosystem carbon cycle model. The resulting analysis quantifies, with uncertainty estimates, the seasonal changes in the net carbon flux of a tropical rainforest which experiences a pronounced dry season. We show that the carbon accumulation in this forest was four times greater in the dry season than in the wet season and that this was accompanied by a 5% increase in the carbon use efficiency. This seasonal response was caused by a dry season increase in gross primary productivity, in response to radiation and a similar magnitude decrease in heterotrophic respiration, in response to drying soils. The analysis also predicts increased carbon allocation to leaves and wood in the wet season, and greater allocation to fine roots in the dry season. This study demonstrates implementation of seasonal variations in parameters better enables models to simulate observed patterns in data. In particular, we highlight the necessity to simulate the seasonal patterns of heterotrophic respiration to accurately simulate the net carbon flux seasonal tropical forest.

Nutrient limitation in rainforests and cloud forests along a 3,000-m elevation gradient in the Peruvian Andes - Joshua B. Fisher; Yadvinder Malhi; Israel Cuba Torres; Daniel B. Metcalfe; Martine J. van de Weg; Patrick Meir; Javier E. Silva-Espejo; Walter Huaraca Huasco (Oecologia, 2013)

Light inhibition of leaf respiration as soil fertility declines along a post-glacial chronosequence in New Zealand: an analysis using the Kok method - Owen K. Atkin; Matthew H. Turnbull; Joana Zaragoza-Castells; Nikolaos M. Fyllas; Jon Lloyd; Patrick Meir; Kevin L. Griffin (Plant and Soil, 2013)

Annual variation in soil respiration and its component parts in two structurally contrasting woody savannas in Central Brazil - Andre Butler; Patrick Meir; Gustavo Saiz; Leandro Maracahipes; Beatriz Schwantes Marimon; John Grace (Plant and Soil, 2012)

Photosynthetic parameters, dark respiration and leaf traits in the canopy of a Peruvian tropical montane cloud forest - Martine Janet van de Weg; Patrick Meir; John Grace; Guilmair Damian Ramos (Oecologia, 2012)

Ecosystem Carbon Storage Across the Grassland–Forest Transition in the High Andes of Manu National Park, Peru - Adam Gibbon; Miles R. Silman; Yadvinder Malhi; Joshua B. Fisher; Patrick Meir; Michael Zimmermann; Greta C. Dargie; William R. Farfan; Karina C. Garcia (Ecosystems, 2010)

No Differences in Soil Carbon Stocks Across the Tree Line in the Peruvian Andes - Michael Zimmermann; Patrick Meir; Miles R. Silman; Anna Fedders; Adam Gibbon; Yadvinder Malhi; Dunia H. Urrego; Mark B. Bush; Kenneth J. Feeley; Karina C. Garcia; Greta C. Dargie; Wiliam R. Farfan; et al. (Ecosystems, 2010)

The effects of water availability on root growth and morphology in an Amazon rainforest - Daniel B. Metcalfe; Patrick Meir; Luiz Eduardo O. C. Aragão; Antonio C. L. da Costa; Alan P. Braga; Paulo H. L. Gonçalves; Joao de Athaydes Silva Junior; Samuel S. de Almeida; Lorna A. Dawson; Yadvinder Malhi; Mathew Williams (Plant and Soil, 2008)

Photosynthetic parameters from two contrasting woody vegetation types in West Africa - Patrick Meir; Peter E. Levy; John Grace; Paul G. Jarvis (Plant Ecology, 2007)

Effects of an induced drought on soil carbon dioxide (CO 2 ) efflux and soil CO 2 production in an Eastern Amazonian rainforest, Brazil - ELENEIDE DOFF SOTTA; EDZO VELDKAMP; LUITGARD SCHWENDENMANN; BRENDA ROCHA GUIMARÃES; ROSIENE KEILA PAIXÃO; MARIA de LOURDES P. RUIVO; ANTONIO CARLOS LOLA da COSTA; PATRICK MEIR (Global Change Biology, 2007)
In the next few decades, climate of the Amazon basin is expected to change, as a result of deforestation and rising temperatures, which may lead to feedback mechanisms in carbon (C) cycling that are presently unknown. Here, we report how a throughfall exclusion (TFE) experiment affected soil carbon dioxide (CO 2 ) production in a deeply weathered sandy Oxisol of Caxiuanã (Eastern Amazon). Over the course of 2 years, we measured soil CO 2 efflux and soil CO 2 concentrations, soil temperature and moisture in pits down to 3 m depth. Over a period of 2 years, TFE reduced on average soil CO 2 efflux from 4.3±0.1 μmol CO 2 m −2 s −1 (control) to 3.2±0.1 μmol CO 2 m −2 s −1 (TFE). The contribution of the subsoil (below 0.5 m depth) to the total soil CO 2 production was higher in the TFE plot (28%) compared with the control plot (17%), and it did not differ between years. We distinguished three phases of drying after the TFE was started. The first phase was characterized by a translocation of water uptake (and accompanying root activity) to deeper layers and not enough water stress to affect microbial activity and/or total root respiration. During the second phase a reduction in total soil CO 2 efflux in the TFE plot was related to a reduction of soil and litter decomposers activity. The third phase of drying, characterized by a continuing decrease in soil CO 2 production was dominated by a water stress‐induced decrease in total root respiration. Our results contrast to results of a drought experiment on clay Oxisols, which may be related to differences in soil water retention characteristics and depth of rooting zone. These results show that large differences exist in drought sensitivity among Amazonian forest ecosystems, which primarily seem to be affected by the combined effects of texture (affecting water holding capacity) and depth of rooting zone.

The regional variation of aboveground live biomass in old‐growth Amazonian forests - YADVINDER MALHI; DANIEL WOOD; TIMOTHY R. BAKER; JAMES WRIGHT; OLIVER L. PHILLIPS; THOMAS COCHRANE; PATRICK MEIR; JEROME CHAVE; SAMUEL ALMEIDA; LUZMILLA ARROYO; NIRO HIGUCHI; TIMOTHY J. KILLEEN; et al. (Global Change Biology, 2006)
The biomass of tropical forests plays an important role in the global carbon cycle, both as a dynamic reservoir of carbon, and as a source of carbon dioxide to the atmosphere in areas undergoing deforestation. However, the absolute magnitude and environmental determinants of tropical forest biomass are still poorly understood. Here, we present a new synthesis and interpolation of the basal area and aboveground live biomass of old‐growth lowland tropical forests across South America, based on data from 227 forest plots, many previously unpublished. Forest biomass was analyzed in terms of two uncorrelated factors: basal area and mean wood density. Basal area is strongly affected by local landscape factors, but is relatively invariant at regional scale in moist tropical forests, and declines significantly at the dry periphery of the forest zone. Mean wood density is inversely correlated with forest dynamics, being lower in the dynamic forests of western Amazonia and high in the slow‐growing forests of eastern Amazonia. The combination of these two factors results in biomass being highest in the moderately seasonal, slow growing forests of central Amazonia and the Guyanas (up to 350 Mg dry weight ha −1 ) and declining to 200–250 Mg dry weight ha −1 at the western, southern and eastern margins. Overall, we estimate the total aboveground live biomass of intact Amazonian rainforests (area 5.76 × 10 6 km 2 in 2000) to be 93±23 Pg C, taking into account lianas and small trees. Including dead biomass and belowground biomass would increase this value by approximately 10% and 21%, respectively, but the spatial variation of these additional terms still needs to be quantified.

Productivity and carbon fluxes of tropical savannas - John Grace; José San José; Patrick Meir; Heloisa S. Miranda; Ruben A. Montes (Journal of Biogeography, 2006)
Aim (1) To estimate the local and global magnitude of carbon fluxes between savanna and the atmosphere, and to suggest the significance of savannas in the global carbon cycle. (2) To suggest the extent to which protection of savannas could contribute to a global carbon sequestration initiative. Location Tropical savanna ecosystems in Africa, Australia, India and South America. Methods A literature search was carried out using the ISI Web of Knowledge, and a compilation of extra data was obtained from other literature, including national reports accessed through the personal collections of the authors. Savanna is here defined as any tropical ecosystem containing grasses, including woodland and grassland types. From these data it was possible to estimate the fluxes of carbon dioxide between the entire savanna biome on a global scale. Results Tropical savannas can be remarkably productive, with a net primary productivity that ranges from 1 to 12 t C ha −1 year −1 . The lower values are found in the arid and semi‐arid savannas occurring in extensive regions of Africa, Australia and South America. The global average of the cases reviewed here was 7.2 t C ha −1 year −1 . The carbon sequestration rate (net ecosystem productivity) may average 0.14 t C ha −1 year −1 or 0.39 Gt C year −1 . If savannas were to be protected from fire and grazing, most of them would accumulate substantial carbon and the sink would be larger. Savannas are under anthropogenic pressure, but this has been much less publicized than deforestation in the rain forest biome. The rate of loss is not well established, but may exceed 1% per year, approximately twice as fast as that of rain forests. Globally, this is likely to constitute a flux to the atmosphere that is at least as large as that arising from deforestation of the rain forest. Main conclusions The current rate of loss impacts appreciably on the global carbon balance. There is considerable scope for using many of the savannas as sites for carbon sequestration, by simply protecting them from burning and grazing, and permitting them to increase in stature and carbon content over periods of several decades.

Soil CO 2 efflux in a tropical forest in the central Amazon - Eleneide Doff sotta; Patrick Meir; Yadvinder Malhi; Antonio Donato nobre; Martin Hodnett; John Grace (Global Change Biology, 2004)
This study investigated the spatial and temporal variation in soil carbon dioxide (CO 2 ) efflux and its relationship with soil temperature, soil moisture and rainfall in a forest near Manaus, Amazonas, Brazil. The mean rate of efflux was 6.45±0.25 SE μmol CO 2 m −2 s −1 at 25.6±0.22 SE°C (5 cm depth) ranging from 4.35 to 9.76 μmol CO 2 m −2 s −1 ; diel changes in efflux were correlated with soil temperature ( r 2 =0.60). However, the efflux response to the diel cycle in temperature was not always a clear exponential function. During period of low soil water content, temperature in deeper layers had a better relationship with CO 2 efflux than with the temperature nearer the soil surface. Soil water content may limit CO 2 production during the drying‐down period that appeared to be an important factor controlling the efflux rate ( r 2 =0.39). On the other hand, during the rewetting period microbial activity may be the main controlling factor, which may quickly induce very high rates of efflux. The CO 2 flux chamber was adapted to mimic the effects of rainfall on soil CO 2 efflux and the results showed that efflux rates reduced 30% immediately after a rainfall event. Measurements of the CO 2 concentration gradient in the soil profile showed a buildup in the concentration of CO 2 after rain on the top soil. This higher CO 2 concentration developed shortly after rainfall when the soil pores in the upper layers were filled with water, which created a barrier for gas exchange between the soil and the atmosphere.